2007
DOI: 10.1182/blood-2006-09-047480
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of FLT3 ligand in immune reconstitution after bone marrow transplantation and high-dose chemotherapy

Abstract: IntroductionThe period of immune deficiency after high-dose chemotherapy and bone marrow (BM) transplantation (BMT) results in significant morbidity and mortality. 1 Whereas early recovery of innate immunity (granulocytes, monocytes/macrophages and natural killer [NK] cells) results in reconstitution of protective immunity against many bacterial pathogens, the levels of functional lymphocytes (components of adaptive immunity) frequently remain abnormal for many months or years. 2 Low levels of B cells and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
(57 reference statements)
5
22
0
Order By: Relevance
“…13,38,39 Notably, compared with WT mice a reduction was observed in total PB reconstitution in Fl Ϫ/Ϫ mice at 16 weeks after transplantation (3.6-fold; Figure 2B). This was almost entirely due to a failure to regenerate primarily B cells and partially T cells in the absence of FL, in agreement with recent studies, 19,40 whereas myeloid reconstitution, representing the best measure of HSC activity because of the short half-life of the myeloid lineage, was not significantly reduced in peripheral blood ( Figure 2B) or in BM ( Figure 2C) of Fl Ϫ/Ϫ recipients. Furthermore, the regeneration of donor-derived LSKCD150 ϩ HSC compartment was not different in Fl Ϫ/Ϫ and WT recipients ( Figure 2D).…”
Section: Role Of Flt3 Ligand In Hsc Maintenance and Expansion After Tsupporting
confidence: 79%
“…13,38,39 Notably, compared with WT mice a reduction was observed in total PB reconstitution in Fl Ϫ/Ϫ mice at 16 weeks after transplantation (3.6-fold; Figure 2B). This was almost entirely due to a failure to regenerate primarily B cells and partially T cells in the absence of FL, in agreement with recent studies, 19,40 whereas myeloid reconstitution, representing the best measure of HSC activity because of the short half-life of the myeloid lineage, was not significantly reduced in peripheral blood ( Figure 2B) or in BM ( Figure 2C) of Fl Ϫ/Ϫ recipients. Furthermore, the regeneration of donor-derived LSKCD150 ϩ HSC compartment was not different in Fl Ϫ/Ϫ and WT recipients ( Figure 2D).…”
Section: Role Of Flt3 Ligand In Hsc Maintenance and Expansion After Tsupporting
confidence: 79%
“…Previous studies have demonstrated that Flt3-Ligand-deficient mice have a reduction in B-cell progenitors in the E14.5 FL. 35 Here we reproduced this finding in Flt3 receptor-deficient (Flk2 2/2 ) mice, and found that although the FL cellularity was not affected (Figure 5B), the frequency of ProB cells was further and dramatically reduced in the E14.5 FL of Flk2 2/2 Csf1r 2/2 double-deficient embryos, when compared with Csf1r 2/2 and Flk2 2/2 single-deficient embryos ( Figure 5C). This finding supports that CSF1R and FLT3 have complementary and critical roles in regulation of the emergence of fetal B-cell progenitors.…”
Section: Concomitant Loss Of Flt3 and Csf1r Leads To A Severe Reductisupporting
confidence: 75%
“…This, however, does not rule out a more crucial role of FL in the GM lineage. In the case of B lymphopoiesis, FL has been shown to have a critical role in B-cell generation after BM transplantation, 42 becomes increasingly important with age, and-most notably IL-7-independent B lymphopoiesis-is strictly FL dependent. 10 Thus, further studies might better reveal conditions in which FL is critically involved in generation and regeneration of cells of the GM lineage.…”
Section: Role Of Flt3 In Early Myelopoiesis 5065mentioning
confidence: 99%